Political Language in Zohran Mamdani’s Victory Speech: A Critical Discourse Analysis - Muhammad Nurfazri; Afita Nur Hayati; Sajidin Sajidin; Dedi Sulaeman; Vini Rizki Nurodiah; Anis Khoirunnisa Syahrussalamah; Hanifa Mawadah; Nabiel Azhari Husaeni (UIN Sunan Gunung Djati Bandung, 2026)
This study examines how progressive political discourse articulates ideology, constructs collective identity, and negotiates power relations between the public and political elites within the context of contemporary democracy. Using a critical qualitative design, the research was grounded in Fairclough’s critical discourse analysis framework: micro, mezzo, and macro. The data were taken from Zohran Mamdani’s victory speech published by the official ABC News YouTube channel. At the micro level, Mamdani frames the electoral victory as the result of a collective struggle through lexical, modal, metaphorical, rhetorical, and agency constructions that delegitimize elites and normalize demands for structural change. At the mezzo level, the speech reconstructs the victory speech genre by linking it to a narrative of ongoing struggle through historical intertextuality and media distribution strategies that position the audience as active political subjects. At the macro level, the discourse operates as an ideological intervention that challenges neoliberal and oligarchic hegemony by asserting democratic socialism as a response to inequality in contemporary democracy. Hence, the study concludes that critical discourse analysis provides a robust analytical lens for uncovering the role of language in both reproducing and contesting power relations, thereby contributing to a more critical understanding of political discourse in democratic contexts.